Stratigraphy and Hydrocarbon Potential of the Central North Atlantic Basin - Jansa, L.; Macqueen, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1978)
Abstract The Central North Atlantic Basin, including most of the lower continental rise areas, should not be regarded as being prospective for hydrocarbons, because of lack of reservoirs, pervasive cementation, insufficient burial, generally low geothermal gradient, and adequate organic matter in only one of the units of the sedimentary fill. The upper parts of the continental rises and the continental slopes in the front of major Lower Cretaceous deltas appear to be prospective. The deeply buried pre-Lage Jurassic succession of shallow- water carbonates beneath the continental slopes and rises appears to offer promise, but until the Deep Sea Drilling Project provides us with better data from the lower parts of the continental margins it is not possible to assess the hydrocarbon potential of these areas.